The feeding ecology of yearling, juvenile and sub-adult Nile crocodiles, Crocodylus niloticus, in the Okavango Delta, Botswana - Wallace, Kevin Michael (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc(Conservation Ecology and Entomology)--University of Stellenbosch, 2006.